Development of Drug Delivery System for Sinus Mucosal Tissues with Mucoadhesive Thermosensitive Sol-Gel Components: Analysis of Evidence from Laboratory to Animal Research - Muhammad Ilham Dhiya Rakasiwi; Ahmad Fadhil Ilham; Natan Kevin Partogu Siagian (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Chronic rhinosinusitis (CRS) is a chronic inflammation of the nasal cavity (12 weeks or more). Until now, the pharmacological treatment for CRS using a nasal drug delivery system (DDS) has been frequently chosen due to the convenience of the administration. However, nasal DDS shows several disadvantages, such as the vulnerability of sinus mucosa to irritation and medication. Purpose: To assess available literature evidence regarding nasal DDS based on sol-gel using P407 and HPMC for CRS therapy. Methods: A literature search on nasal DDS development using sol-gel thermosensitive mucoadhesive P407 and HPMC was conducted through Pubmed and Proquest journal databases. The supporting articles were searched using specific keywords with inclusion criteria. Results: Sol-gel with P407 (15,5% w/w) and HPMC (0,4% w/w and 0,7% w/w) shows gelation temperature 34.18±0.06oC and 32.76±0.45oC respectively, and virtually clear gel. Rheological evaluation of sol-gel DDS shows modulus G’>G” at 8oC (solution form), while at 32oC shows modulus G’<G” (elastic gel form). In vitro test of dexamethasone release shows velocity 70-81 μg/cm2 h−1/2 after 72 hours of administration. Ex vivo test shows slow permeation of dexamethasone at sinus mucosa for 8 hours. Conclusion: Based on the in vitro and ex vivo models, the thermosensitive mucoadhesive gel composed of p407 and HPMC produced extended drug release profiles in conditions mimicking the human nasal cavity, which indicated their suitability for treating a range of conditions affecting the nasal cavity/sinuses.